Fermentation of Jatropha curcas solid waste with Aspergillus niger - Kahirul Farihan, Kasim; Nurul Iwani, Alawi; Mahmad Nor, Jaafar, Assoc. Prof. Dr.; Mohamed Zulkali, Mohamed Daud (Sarawak Biodiversity Centre & Malaysian Biotechnology Corporation, 2011)
Biodiversity and Biotechnology Symposium organized by Sarawak Biodiversity Centre & Malaysian Biotechnology Corporation, 19th-21th November 2008 at Hilton Hotel, Kuching, Sarawak, Malaysia.